ANALISIS KADAR PROTEIN PADA ASI DAN SUSU FORMULA UNTUK USIA 0-6 BULAN - Zuhairiah Zuhairiah; Yosy Cinthya Eriwaty Silalahi; Siti Nurbaya (Jurnal Farmanesia, 2019)
Breast milk has advantages compared to other milk, including guaranteed clean liness, the temperature of breast milk is the same as body temperature, rich in food essences that accelerate the growth of brain cells and the development of the nervous system. This study aims to determine the protein content in breast milk and infant formula and to determine the difference in higher protein between breast milk and infant formula. The samples used in this study were breast milk for 1 week, breast milk for 3 months, formula A, formula B and formula C. The results of this study obtained measurements made that maximum absorption was obtained at a wavelength of 542.00 nm, Samples of breast milk were 1 week. and breast milk for 3 months which showed a significant difference in protein content. Sample A, Sample B, and sample C milk had lower protein content than Sample 1 week breast milk and 3-month breast milk. The conclusion of this study is that there are a certain amount of protein in breast milk and infant formula, namely 2.77±0.0276 g/100 g in 3-month breast milk, 2.26±0.0126 g/100g in 1 week breast milk, 1 ,37±0.0308 g/100g in formula milk sample A 1.36±0.0247 g/100g milk formula B and 1.44±0.0728 g/100 g in formula C and There is a significant difference in protein content. significant in breast milk, infant formula for samples A, B and C.